Characterization of DD-carboxypeptidase function in mycobacteria: genetic knockout and recombinant protein production - Ismail, Zaahida Sheik (My University, 2016)
Tuberculosis (TB), a disease caused by the pathogenic bacterium Mycobacterium tuberculosis (Mtb), is responsible for killing over one million people each year with an alarming number categorized as multidrug resistant (MDR) or extensively drug resistant (XDR) infections. These high numbers, coupled with other factors such as the ability of Mtb to adapt to its host, its synergistic relationship with Human Immunodeficiency Virus (HIV) and the protracted treatment regimen required to treat TB has resulted in the urgent need for new TB drugs. In this regard, the peptidoglycan (PG) layer of the mycobacterial cell wall, which requires an array of enzymes for synthesis of this mesh-like polymer, have been of particular interest. The PG consists of sugars cross-linked by stem peptides and is synthesized, cross-linked and remodeled by carefully regulated enzymes such as penicillin binding proteins (PBPs) which perform the final crosslinking step in PG biosynthesis. This study focuses on a specific group of low molecular weight PBPs, namely the DD-carboxypeptidases (DD-CPases), which are responsible for regulating the amount of cross-links found in the PG by cleaving the terminal D-Alanine (D-Ala) from the stem peptide of nascent PG units. To date, these proteins have remained largely uncharacterized in mycobacteria. To investigate the functions of these proteins in Mycobacterium smegmatis, two double knockout mutants lacking different combinations of the DD-CPase-encoding genes (MSMEG_1661, MSMEG_2432 and/or MSMEG_2433) were created using two-step allelic exchange and assessed using a range of phenotypic analyses. In addition recombinant protein production of these DD-CPases as well as MSMEG_6113 was attempted. We were unable to create a double knockout mutant lacking both MSMEG_2432 and MSMEG_2433 from an existing single mutant strain, suggesting that the operonic structure of these two genes may require a different approach. We were able to generate two double knockout mutants, ΔMSMEG_1661 ΔMSMEG_2432 and ΔMSMEG_2433 ΔMSMEG_1661, lacking two DDCPases. Southern blot and gene expression analyses confirmed loss of the respective genes from M. smegmatis. The ΔMSMEG_1661 ΔMSMEG_2432 mutant and ΔMSMEG_2433 ΔMSMEG_1661 mutant displayed no alterations in colony morphology, biofilm formation, sliding motility and sodium dodecyl sulphate (SDS) sensitivity. However, loss of two DD-CPases resulted in increased sensitivity of M. smegmatis to vancomycin and a range of β-lactams antibiotics. Analysis of cellular morphology using transmission electron microscopy (TEM) demonstrated that the septum was fully formed in all strains but in some cases was not degraded during daughter cell separation. Scanning electron microscopy (SEM) and spatial localization of new PG units using BODIPY-labeled vancomycin revealed that late division processes were hampered in these double knockout mutants with new PG inserted across the cell as well as cells with multiple unresolved septa. To create recombinant derivatives of MSMEG_6113, MSMEG_1661, MSMEG_2432 and MSMEG_2433, proteins were His-tagged and purified using affinity chromatography. However, under all conditions tested soluble protein could not be acquired. Collectively, these data provide the first evidence that the DD-CPases of M. smegmatis may play a direct role in the late cell division process that lead to daughter cell separation in mycobacteria.
A dissertation submitted to the Faculty of Health Science, University of Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Medicine. 2016
Keywords: Mycobacterium; Tuberculosis